Distribution of tyrosine Hydroxylase-Immunoreactive neurones in the diencephalon and mesencephalon of the coypu (Myocastor coypus) - Sánchez, H. L. (2000)
The aim of the present study was to examine the catecholaminergic neurones located within the midbrain of the coypu, a South American hystricomorph rodent. The neuronal distribution of the catecholaminergic systems and morphological parameters of the immunostained cell bodies and fibres were investigated, using an immunohistochemical method. The brains of five coypu were fixed, immersed in gelatine-glycerol and cut in 40-μm slices using a freezing microtome. Samples were processed with ultrasound-based antigen retrieval and stained with labelled antityrosine hydroxylase monoclonal antibody. An image analyser was used to measure the neuronal bodies. The catecholaminergic neurones of the tuberoinfundibular system were mainly observed in the arcuate and periventricular nuclei with their axons projecting towards to the median eminence; they represented 28% of the global population of tyrosine hydroxylase-immunoreactive cells observed. Significant morphological differences were observed in comparison with the other two studied systems. Fifty per cent of total catecholaminergic neurones were detected in the nigrostriatal system distributed in the reticular and compact substance nigra. Most neuronal bodies had a fusiform aspect. The immunoreactive neurones of the mesolimbic system represented 22% of the total population. They were distributed around the interpeduncular nucleus. Two types of morphologically different catecholaminergic systems of the brain were established: hypothalamic neurones located in the periventricular and arcuate nuclei and mesencephalic neurones located in the substance nigra and interpeduncular nuclei. These systems showed morphological and probably physiological-pharmacological differences.